The Effect of Relationship Marketing on Customer Loyalty at PT. Hadji Kalla Sengkang Branch - Amin, Febriana Awaliyah; Darwis, Muh; Baharuddin, Aris (Universitas Negeri Makassar, 2026)
This study aims to determine how the influence of relationship marketing on customer loyalty at PT. Hadji Kalla Sengkang Branch. To achieve this goal, researchers use indicators to measure these variables. In the relationship marketing variable , the indicators used are trust , commitment , communication , and conflict handling . As for the customer loyalty variable, the indicators used are repeat purchases , permanent purchases ( retention ), and recommending to others ( referrals ). In this study the research method used was quantitative method, with data collection techniques through observation, questionnaires, and documentation. The sample used was 97 respondents, resulting from the Slovin formula. The data were obtained from the results of the research and processed using data analysis and the help of the SPSS version 25 program which consisted of validity and reliability tests, simple linear regression analysis and the coefficient of determination. The results showed that the indicators used for each variable, namely relationship marketing (X) were in the very good category and the customer loyalty variable (Y) was in the good category. This shows that the relationship marketing variable has a significant influence on customer loyalty at PT. Hadji Kalla Sengkang Branch. This is proven based on the t test and the coefficient of determination test on the data obtained.